Knowledge on functions of school landscape on learning achievements / Salina Mohamed Ali ... [et al.] - Mohamed Ali, Salina; Awang, Abd. Hair; Rostam, Katiman; Nawawi, Abdul Hadi (Faculty of Architecture, Planning and Surveying, 2016)
The main objective of this study is to identify the knowledge on functions of the schools’ landscapes in the learning process. For the purpose of this study, data were collected through field observations using a checklist at 104 schools. Structured interviews were conducted with school managers and secondary data was obtained from various agencies. Results showed that the function of landscapes in assisting learning is at a high score, and rural schools are slight better than urban schools. There are a variety of learning activities held within the schools’ landscape, mainly flower planting, followed by camping activities, cooking and carpentry. There is a significant relationship between the function of landscapes assisting in the learning process and academic achievements. This proves that landscape has an important role in the learning process and should be emphasised to create awareness amongst the school’s community.